Alice Getz: capstone - Getz, Alice, artist (Colorado State University. Libraries, 2014)
The artist's statement: Engrained (series - ink and mixed media on wood) The wooden works started with a series of ideas brought on by wood grain, combined with careful thoughts about meaning, and human manipulation. To see wood grain requires the splitting and manipulation of the natural tree. Human influence is already present in wood grain, but the textures and patterns are something we also find universally beautiful and relatable. People influence and affect each other and the world around them constantly. The idea of natural paths and universal collective subconscious and the sharing of ideas and thoughts is present in the idea that we share and see many of the same things, and create in our own minds separate and individual imagery and imagination out of the things we encounter, be it forms, shapes, lines, implied figures, moods, ideas, and experiences. These are all part of human experience. I took a simultaneous interest in these works for Taoist principals, including the uncarved block and following a path of highest potential and lesser resistance. The final idea is one that has been present since the beginning of human culture of creating and emphasizing forms from those that already exist. It is human nature to want to leave our own mark and express a personal perspective. In trinity I expressed an idea of stability, collective subconscious, and individual expression of thoughts- while considering all of these influences in the making of deliberate marks and embellishment of particular forms. Adaptation (ongoing- flux) This work is continuous, 2007 to the present day. It utilizes mixed media and a series of techniques, favored in different time periods during these years. Adaptation represents a transitional period of time. A period of euphoric disillusionment and self-sabotage is the first step in the change. Whether the euphoria is caused by general youth, is drug induced, an illusion or false perspective of safety, or a reliance on any vice, it still is a type of shelter or confusion that separates an entity from reality and from striving for change. The space within the tree IS a striving for change. It is a time period of self-actualization, there is a type of safety and loss in the phase of changes, no figures or forms are present in the center, because it represents a loss of familiarity and a chance for reformation or to be pressed into worse circumstances if there is a strong resistance to change. Change and growth come of learning to live without roots of life. They both become the roots and become our reasons for appreciating stability, familiarity and structure when they return. The other side is the outcome of change, unknown sometimes, viewed before we can clearly experience it as a source of apprehension and a yearning for avoidance, that later becomes a source of familiarity and strength.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.